CaMKIIβ is localized in dendritic spines as both drebrin‐dependent and drebrin‐independent pools. Issue 2 (11th June 2018) - Yamazaki, Hiroyuki; Sasagawa, Yoshio; Yamamoto, Hideyuki; Bito, Haruhiko; Shirao, Tomoaki
Abstract: Drebrin is a major F‐actin binding protein in dendritic spines that is critically involved in the regulation of dendritic spine morphogenesis, pathology, and plasticity. In this study, we aimed to identify a novel drebrin‐binding protein involved in spine morphogenesis and synaptic plasticity. We confirmed the beta subunit of Ca 2+ /calmodulin‐dependent protein kinase II (CaMKIIβ) as a drebrin‐binding protein using a yeast two‐hybrid system, and investigated the drebrin–CaMKIIβ relationship in dendritic spines using rat hippocampal neurons. Drebrin knockdown resulted in diffuse localization of CaMKIIβ in dendrites during the resting state, suggesting that drebrin is involved in the accumulation of CaMKIIβ in dendritic spines. Fluorescence recovery after photobleaching analysis showed that drebrin knockdown increased the stable fraction of CaMKIIβ, indicating the presence of drebrin‐independent, more stable CaMKIIβ. NMDA receptor activation also increased the stable fraction in parallel with drebrin exodus from dendritic spines. These findings suggest that CaMKIIβ can be classified into distinct pools: CaMKIIβ associated with drebrin, CaMKIIβ associated with post‐synaptic density (PSD), and CaMKIIβ free from PSD and drebrin. CaMKIIβ appears to be anchored to a protein complex composed of drebrin‐binding F‐actin during the resting state. NMDA receptor activation releases CaMKIIβ from drebrin resulting in CaMKIIβ association with PSD. Abstract : Drebrin stabilizes actin cytoskeleton in dendritic spines and is involved in the spine morphogenesis, pathology, and plasticity. In this study, we identified CaMKIIβ as a novel drebrin‐binding protein. CaMKIIβ is interacted with drebrin in the center region of dendritic spines under basal condition. NMDA receptor activation releases CaMKIIβ from drebrin resulting in its association with PSD, while NMDA receptor activation induces drebrin exodus from dendritic spines. Our findings suggest that there are distinct CaMKIIβ pools in dendritic spines, drebrin‐dependent and ‐independent CaMKIIβ. The disappearance of the drebrin‐dependent CaMKIIβ pool may contribute to the initiation of synaptic plasticity.